A Comparative Study of Orotracheal Intubation Guided by Airtraq and McCoy Laryngoscope in Patients with Rigid Cervical Collar In-situ Simulating Cervical Immobilization for Traumatic Cervical Spine Injury - Akhil Diwan; Shobha Purohit (Indian Journal of Neurosurgery)
Background Immobilization of cervical spine is of utmost importance in patients with cervical injury, making intubation a difficult task due to the application of cervical collar. This study was done to assess which laryngoscope (Airtraq or McCoy) is better for intubation and prevents the deleterious effects of hypoxia by comparing the intubation time. Methods A prospective interventional randomized study was undertaken in 60 adult patients of American Society of Anesthesiologists (ASA) grade I and II, aged between 20 and 50 years, scheduled for various surgical procedures requiring tracheal intubation for anesthesia. Patients were randomly allocated to undergo intubation with either the Airtraq (Group A; n = 30) laryngoscope or McCoy (Group B; n = 30). Patients were intubated following the standard anesthetic protocol, and the differences in duration of intubation, changes in the hemodynamic parameters in response to intubation, modified intubation difficulty score, and airway complications between the Airtraq and the McCoy laryngoscope were compared. Results Overall intubation success rates were 100% with both devices and a similar number of intubation attempts were required. Though the mean time required for successful intubation was less with the Airtraq (25.2 ± 5.11 seconds) than the McCoy laryngoscope (27.3 ± 4.47 seconds); it was statistically insignificant (p = 0.14). Intubation difficulty score and ease of insertion were significantly less in Airtraq laryngoscope when compared with McCoy laryngoscope. Increase in the heart rate and mean arterial pressure was significantly more just after intubation with McCoy in comparison with Airtraq laryngoscope. However, the frequencies of airway complications were similar. Conclusion Intubation time despite being lesser with the Airtraq than the McCoy laryngoscope was statistically insignificant, and overall success rates between the two devices were similar.